A Identidade Profissional pela Tessitura do Discurso de Funcionários/as da Escola Pública Estadual no Programa Profuncionário - LOPES, Claudia Simone Carneiro (2014)
This research aims to analyze the professional identity of staff / the school of basic education ( merendeiros / as , guards , secretaries / as, janitors / as, employees / those responsible for multimedia classrooms , video and library) , through official speeches and discourses produced by these / those in the process of training in Profuncionário program - Initial Training program for Service Professionals of Basic Education of the Public Education System . This is the need to know how far the curriculum of the program through the training process , contributes to the construction of identities . Thus, our point of reflection focuses on understanding of professional identity as something plural intertwines social representations around each subject . Therefore, to carry out the research , we seek to support us in the categories of analysis : identity ( Hall ; Silva ) , memory ( Halbwachs , Bosi ) , training ( Josso ; Souza ) and resume ( Sacristan ) , through which we aim to understand the universe construction of discourses involving the identity of the school officials . To the fabric of the study, we initially speeches of the history of these employees in Brazilian education , the creation of the first Initial training program for these subjects , and consequent analysis of the relationship of the training process , through the curriculum of the program and the constitution of identities these / the staff / the . We proceed to the analysis of documents , photos and records of activities developed during training, in order to try to understand that identities are articulated in the construction of these individuals as professionals. Also resorted to the technique of open interviews and the analysis of personal narratives , through the eye on the training and memorials on the voices of employees subject / the . In this study , organized in four chapters , we present the construction of the object and its texture , as results of our trajectory approach .